A117 SQUAMOUS CELL CARCINOMA (SCC) IN A PATIENT WITH FISTULIZING CROHN'S DISEASE (CD): AN UNUSUAL CAUSE FOR HYPERCALCEMIA. (1st March 2018) - Rai, M; Al Ghamdi, S; Erin, K; Kenneth, C
Abstract: Background: Fistulizing disease in CD is a common occurrence, affecting up to 50% of CD patients after 20 years. Malignant transformation is a rare complication in perianal fistulas, and has also been reported to arise from enterocutaneous fistulae (EF). Aims: We present a patient with complex fistulizing CD who presented with hypercalcemia secondary to a rapidly enlarging invasive abdominal SCC. Methods: A comprehensive literature search identified 2 cases of SCC associated with EFs in patients with CD. Neither of these patients presented with metabolic abnormalities. Results: A 44-year-old with a history of longstanding ileocolonic penetrating CD underwent multiple small bowel resections and was on home TPN for short gut syndrome. For the past several years her CD was managed with Azathioprine monotherapy, she was biologic-naïve. She presented with a 4-month history of a progressive lower abdominal pain. A CT scan initially revealed a complex mass in the lower abdomen and pelvis measuring 8.3 x 9.6 x 7.5 cm, with a fluid attenuating center encasing small bowel and spreading anteriorly into the abdominal wall. An infectious collection was initially suspected, but she did not respond to 2 courses of antibiotics. She continued to develop progressive lower abdominal pain and increased persistent purulent discharge originating from a long-standing EF. Blood work revealed chronic iron deficiency anemia (Hb 80g/L, ferritin 15 pmol/L) normal white blood cell count and platelets, negative inflammatory markers, low albumin (30 g/L) and elevated corrected calcium (3.9mmol/L). Phosphate, magnesium and PTH levels were normal. MRI revealed the abdominal mass had grown over 2 weeks to 13.6 x 13.1 x 15.4 cm with internal necrosis and invasion to the urinary bladder, colon, anterior abdominal wall, pelvic sidewall and uterus. Percutaneous biopsy showed invasive SCC with negative p16 staining, making HPV-associated SCC less likely. CT scan of her chest did not reveal a lung primary and a bone scan was normal. The origin of the tumour was thought to be her longstanding EF. Due to the extent of the mass, she was not a candidate for surgical intervention. The patient's hypercalcemia was treated with intravenous fluids and bisphosphonates and was patient was started on neoadjuvant chemoradiation. Conclusions: SCC of the anus and skin have been reported in CD. SCC development in Crohn's disease patients with chronic fistulas is a rare entity with a poor outcome. Delayed wound healing, constant mucosal regeneration with high cell turnover rates or immunosuppressive therapies may play a role in malignant transformation. Physicians should be aware of the malignancy potential in patients presenting with persistent pain, unhealing fistulas and metabolic abnormalities, as delayed diagnosis contribute to limited treatment options and poor outcomes. Funding Agencies: None